THE COMBINED EFFECT OF PARTICLE SIZE AND STABILIZER OF BOFS ON HIGH-SULFATE BEARING KAOLIN CLAY - Abzal, Aliya (Nazarbayev University School of Engineering and Digital Sciences, 2025)
Researchers have used the stabilization of high-sulfate-bearing soils with traditional calcium-based stabilizers. However, recent failures in structures like heaving and the formation of expansive minerals have raised concerns about the long-term stability of calcium-based stabilizers in sulfate-rich environments. Given these limitations, alternative stabilizing agents have gained attention. One of them is Basic Oxygen Furnace Slag (BOFS), which has emerged as a promising alternative due to its pozzolanic properties and ability to mitigate sulfate-induced reactions. The study aims to evaluate the performance of Basic Oxygen Furnace Slag (BOFS) as an alternative to traditional calcium-based stabilizers. Correspondingly, the primary goal of this research is to study the combined effect of particle size and stabilizer effect of BOFS on the mechanical properties and durability characteristics of stabilized soil. Further, the developed experimental program consisted of geotechnical characterization, unconfined compressive strength (UCS), one-dimensional swelling, and mineralogical examination using X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). Kaolin clay, which is made artificially with high sulfate content, was stabilized mechanically using BOFS of different particle size fractions, and the effects of curing days, particle sizes, and volumetric and mass-based BOFS addition were evaluated. Unconfined compressive strength (UCS)test results demonstrated a significant increase in compressive strength, particularly in samples with finer particle size fractions. 1D-Swelling test also proved the hypothesis that BOFS as a stabilizer can effectively reduce volume changes, with the finest BOFS fractions minimizing the expansiveness of the soil. XRD and SEM analyses confirmed the formation of cementitious compounds such as calcium silicate hydrates (CSH), contributing to strength enhancement and reduced swelling, as well as the formation of expansive ettringite minerals.
Keywords: Basic Oxygen Furnace Slag (BOFS); High-sulfate bearing soils; Kaolin Clay; Swelling behavior; Unconfined Compressive Strength (UCS); Soil Stabilization; Particle Size; Strength estimation; type of access: embargo